Meeting children's needs through literature - Canon, Kristine (The RAP Journal, 2006)
In this paper, an award-winning author shares her thoughts about how literature and books can meet the various needs of children, even material ones. She points out that the magic of good literature results from the weaving of several elements-- the story behind the needle, the theme the thread, and the illustration the pattern that is produced.